Pelatihan dan Pendampingan Pengendalian Mutu Produk Virgin Coconut Oil - Mufid, Mufid; Windy Mustikarini, Anugrah; Kurnia Pratiwi, May; Rubianto, Luchis; Hermien Suharti, Profiyanti (LPkM Universitas Bakrie, 2024)
Virgin Coconut Oil (VCO) is a processed coconut fruit product that can be utilized both as raw material and consumed directly. The many benefits of VCO make VCO a product that is in demand and worth selling. Family Welfare Empowerment (PKK) RT 05 RW 07 Bunulrejo Village, Malang City, East Java, has received technical guidance on making VCO by a community service team from the Department of Chemical Engineering, State Polytechnic of Malang. VCO will be produced on a home industry scale with the availability of coconut raw materials that are easily obtained from surrounding markets. The purpose of this assistance and training is to equip partners to conduct quality testing of VCO products according to the Indonesian National Standard (SNI) 7381:2008 and understand the Standard Operating Procedure (SOP) for quality control of VCO on a home industry scale in maintaining the quality of VCO produced. The methods used were lectures, discussions, training on quality testing of VCO products, namely pH test and organoleptic test according to Indonesian National Standard (SNI) 7381:2008 and surveying the results of satisfaction and improvement of partner skills. The results of the activities obtained were increased understanding and skills of participants in quality control of VCO products. Partners can conduct a pH test of VCO with a pH of 5 and the results of the organoleptic test of VCO products obtained for taste, appearance and odor are in the normal category and in accordance with SNI standards. After the mentoring, based on the survey results 80% of participants strongly agreed and the rest agreed that there was an increase in independence or additional knowledge and skills in partners, and 90% of participants strongly agreed and the rest agreed that they felt satisfaction with the PPM activities that had been carried out.